2019
DOI: 10.1016/j.neuron.2019.09.018
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Neuropathic Pain from Model Organisms to Clinical Application

Abstract: Neuropathic pain (NeuP) arises due to injury of the somatosensory nervous system and is both common and disabling, rendering an urgent need for non-addictive, effective new therapies. Given the high evolutionary conservation of pain, investigative approaches from Drosophila mutagenesis to human Mendelian genetics have aided our understanding of the maladaptive plasticity underlying NeuP. Successes include the identification of ion channel variants causing hyper-excitability and the importance of neuro-immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 205 publications
(251 reference statements)
1
62
0
Order By: Relevance
“…Here, with our platform we observed both homogeneity in behavioral responses across six genetically distinct mouse lines, as well as two outlier strains with responses that mapped outside the range of those six. A wealth of prior literature demonstrated that individual differences in responsiveness to pain in both mice and humans, are driven in part by allelic variation in genes important for pain processing [28,29]. In regards to the mouse, studies carried out twenty years ago testing pain sensitivity across 11 inbred lines using 12 behavioral read-outs, revealed that depending upon the sensory modality tested, and whether the test was performed before or after injury to the somatosensory system, genotype appeared to influence mouse pain behaviors [30].…”
Section: Discussionmentioning
confidence: 99%
“…Here, with our platform we observed both homogeneity in behavioral responses across six genetically distinct mouse lines, as well as two outlier strains with responses that mapped outside the range of those six. A wealth of prior literature demonstrated that individual differences in responsiveness to pain in both mice and humans, are driven in part by allelic variation in genes important for pain processing [28,29]. In regards to the mouse, studies carried out twenty years ago testing pain sensitivity across 11 inbred lines using 12 behavioral read-outs, revealed that depending upon the sensory modality tested, and whether the test was performed before or after injury to the somatosensory system, genotype appeared to influence mouse pain behaviors [30].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral Fibers Increase of peripheral sensitivity Expression of endogenous ligands and receptors on injured nerve target Increase of NF-kB pathway activity Promote the production of leukotriene ▶fig. 1 Pathophysiology of neuropathic pain [21][22][23][24][25][26][27][28][29]. lysophosphatidic acid (LPA), gamma-aminobutyric acid (GABAergic) interneurons, nuclear factor 'kappa-light-chain-enhancer' (NF-κB).…”
Section: Dorsal Root Ganglia Increase Of Calcium Concentration and Nementioning
confidence: 99%
“…Successes include the identification of ion channel variants causing hyper-excitability and the importance of neuro-immune signaling. Recent developments encompass improved sensory phenotyping in animal models and patients, brain imaging, and electrophysiology-based pain biomarkers, the collection of large well-phenotyped population cohorts, neurons derived from patient stem cells [21].…”
Section: Pathophysiology Of Neuropathic Painmentioning
confidence: 99%
“…It is generally accepted that altered somatosensory and nociceptive perception in neuropathic pain result from still incompletely understood changes at the dorsal horn circuitry [50][51][52]. Several of the suspected changes occur in second order intrinsic dorsal horn neurons.…”
Section: No Overt Changes In the Translatome Of Spinal Neurons After mentioning
confidence: 99%